POTENSI EKSTRAK DAUN KARUK (Piper sarmentosum) SEBAGAI INSEKTISIDA NABATI HAMA ULAT GRAYAK (Spodoptera litura) - Rangga Eka S. P; Moerfiah .; Triastinurmiatiningsih . (Universitas Pakuan, 2018)
The purpose of this study was to determine the activity of the leaf extract of Piper sarmentosum on mortality and damage levels by pest armyworm (Spodoptera litura). This research was conducted at the Laboratory of Biology, Faculty of Mathematics and Natural Sciences, Pakuan University, Bogor. This study uses a completely randomized design (CRD), with four levels of extract concentration, that is 0% as control, 30%, 40% and 50%. Each treatment was repeated four times. The variables measured were mortality rates, the extent of damage the leaves, and larval growth. A concentration of EDK 50% showed activity in killing the armyworm by 38%. The lowest level of damage is 5%, with an average growth rate to its lowest larvae by 0.8 cm with the provision of treatment EDK 50%, and the higest level of damage is 75% by a concetration of EDK 30% treatments.